Do Earnings Management and Audit Committee Have an Effect on the Firm Value? - Dudi Pratomo; Daniel Adventheo Sudibyo (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2023)
The stock price is used as a consideration for investors to invest in a company. During the COVID-19 pandemic, stock prices fell thus it became a special concern for investors. The stock price can show the high and low of the firm value. A company that has a high firm value can reflect the company’s good performance and it able to provide prosperity to investors. In the future, highly firm value can make the markets and investors confident on the company’s prospects and performance. This study aims to determine the effect of earnings management and the audit committee on the firm value with control variables of profitability, leverage, and firm size in the companies indexed LQ45 on the Indonesia Stock Exchange 2016-2020. The data used were obtained from annual reports on the official website of the Indonesia Stock Exchange and the company’s official website. The populations are the companies indexed LQ45 on Indonesia Stock Exchange. The sampling technique used purposive sampling and obtained as many as 24 companies in 5 years, the total samples are of 120 companies. The analytical method used is panel data regression analysis. The result shows that earnings management and audit committee with profitability, leverage, and firm size as control variables have a simultaneous effect on the firm value. Meanwhile, earnings management and audit committee with profitability, leverage, and firm size as control variables have no partial effect on the firm value at the LQ45 indexed companies on Indonesia Stock Exchange in 2016-2020.